Case Report: Lung Adenocarcinoma Initially Presenting With Cutaneous and Subcutaneous Metastases - Wang, Jingjing; Wu, Ruolin; Liu, Fang; Yang, Liu; Hu, Fan; Wu, Zhijian; Gao, Zairong; Xia, Xiaotian (Frontiers in Oncology, 2022)
Cutaneous and subcutaneous soft tissue metastases are rare in lung adenocarcinoma and suggest poor prognosis. We report a patient with lung adenocarcinoma who initially presented with cutaneous and subcutaneous metastases to the abdomen that were initially presumed to be herpes zoster and an occult subcutaneous soft tissue mass. Because the lesions progressed over 3 weeks despite routine herpes zoster treatment, magnetic resonance imaging was performed and showed a presumed sarcoma; however, 18F-fluourodeoxyglucose positron emission tomography/computed tomography demonstrated pulmonary lesions. Biopsy of the abdominal lesion confirmed poorly differentiated lung adenocarcinoma. Early diagnosis of soft tissue metastasis can be difficult. Clinicians should suspect internal organ malignancy when a progressive cutaneous or subcutaneous soft tissue lesion is encountered.